Variable Addition and Lagrange Multiplier Tests for Linear and Logarithmic Regression Models - Godfrey, L. G.; McAleer, Michael; McKenzie, C. R. (The Review of Economics and Statistics, 1988)
L. G. Godfrey, Michael McAleer, C. R. McKenzie, Variable Addition and Lagrange Multiplier Tests for Linear and Logarithmic Regression Models, The Review of Economics and Statistics, Vol. 70, No. 3 (Aug., 1988), pp. 492-503